2022
DOI: 10.1002/path.5984
|View full text |Cite
|
Sign up to set email alerts
|

A map of the spatial distribution and tumour‐associated macrophage states in glioblastoma and grade 4 IDH‐mutant astrocytoma

Abstract: Tumour‐associated macrophages (TAMs) abundantly infiltrate high‐grade gliomas and orchestrate immune response, but their diversity in isocitrate dehydrogenase (IDH)‐differential grade 4 gliomas remains largely unknown. This study aimed to dissect the transcriptional states, spatial distribution, and clinicopathological significance of distinct monocyte‐derived TAM (Mo‐TAM) and microglia‐derived TAM (Mg‐TAM) clusters across glioblastoma‐IDH‐wild type and astrocytoma‐IDH‐mutant‐grade 4 (Astro‐IDH‐mut‐G4). Single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 59 publications
1
13
0
Order By: Relevance
“…However, the Iba1‐fluorescent area is not significantly different between the two genotypes in the tumor‐brain interface, the ABR1‐4 (Figure 2c,d), and the contralateral area (Figure 2b,d). Notably, the distribution of GAMs at the tumor‐brain interface is denser compared to the rim of the tumor (Figure 2c,d), similar to the data that have been reported in patient glioblastoma tissue (Yin et al, 2022), indicating that the GL261 glioblastoma mouse model represents the clinical features of GAMs distribution.…”
Section: Resultssupporting
confidence: 87%
“…However, the Iba1‐fluorescent area is not significantly different between the two genotypes in the tumor‐brain interface, the ABR1‐4 (Figure 2c,d), and the contralateral area (Figure 2b,d). Notably, the distribution of GAMs at the tumor‐brain interface is denser compared to the rim of the tumor (Figure 2c,d), similar to the data that have been reported in patient glioblastoma tissue (Yin et al, 2022), indicating that the GL261 glioblastoma mouse model represents the clinical features of GAMs distribution.…”
Section: Resultssupporting
confidence: 87%
“…Moreover, the strict sample preparation requirement for large-scale scRNA-Seq analysis on human GBM tumor tissues is still challenging ( 107 , 108 ). Finally, the spatial distribution of TAMs can generate additional heterogeneity, since specific local niches are able to affect TAM distribution and functional polarization ( 109 , 110 ). For example, IBA1 + TMEM119 – CXCL3 + macrophages are predominantly located at perinecrotic areas and express genes involved in inflammatory program and glycolysis, whereas IBA1 + TMEM119 + CCL4 + microglia are enriched at the tumor-brain interface and express chemoattractant-encoding genes involved in T cell recruitment ( 110 ).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the spatial distribution of TAMs can generate additional heterogeneity, since specific local niches are able to affect TAM distribution and functional polarization ( 109 , 110 ). For example, IBA1 + TMEM119 – CXCL3 + macrophages are predominantly located at perinecrotic areas and express genes involved in inflammatory program and glycolysis, whereas IBA1 + TMEM119 + CCL4 + microglia are enriched at the tumor-brain interface and express chemoattractant-encoding genes involved in T cell recruitment ( 110 ). Characterization of TAM spatial distribution and identification of the context-dependent niche signals that drive TAM activation and polarization are two remaining challenges.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found that there were a large number of TAMs in GBM. There is a correlation between TAM density and glioma grade, indicating that TAMs support tumor development (51,52). Interestingly, negative correlations were found in this study between MLLT11 expression and M2 macrophages, as well as M1 macrophages.…”
Section: Discussionmentioning
confidence: 41%